PERBEDAAN EFEKTIVITAS SENAM JANTUNG SEHAT DAN SENAM LANSIA TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI PUSKESMAS NUSA INDAH KOTA BENGKULU TAHUN 2018 - Devi Listiana; Buyung Keraman; Yuki Manto (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2019)
Hypertension is a heart disease and blood vessels that are marked by an increase in blood pressure. One non-pharmacological therapy for hypertension is boarding. Elderly gymnastics is a series of regular and directed and planned tone movements performed individually or groups. The general objective in this study was to study the differences in the effectiveness of elderly gymnastics and healthy heart gymnastics to decrease blood pressure in hypertensive patients at the Nusa Indah Health Center Bengkulu City in 2018. Was the amount of this study using a quasi experimental design of pre and post test. The population in this study were all hypertensive patients in gymnastics members at the Nusa Indah Health Center in Bengkulu City in 2018.Sampling was taken from the entire population. Has research using the Shapiro-Wilk test showed that the value p = 0.247 (>a=0.05) meaning that there was no difference in exercise effectiveness. Elderly and healthy cardiac gymnastics against a reduction in systolic blood pressure in patients hypertension at Nusa Indah Health Center Bengkulu City in 2018. The value p = 0.450 (>a=0.05) means that there is not difference in the effectiveness of elderly gymnastics and healthy heart gymnastics against a decrease in diastolic blood pressure in hypertensive patients at Nusa Indah Health Center in Bengkulu City in 2018. Expected to hypertensive patients to more regularly take part in gymnastics activities to maintain blood pressure stability.Â Keywords : Elderly Gymnastics, Healthy Heart Gymnastics, Hypertension